The Influence of Front-of-Package Nutrition Labeling on Consumer Behavior and Product Reformulation - Roberto, Christina A; Ng, Shu Wen; Ganderats-Fuentes, Montserrat; Hammond, David; Barquera, Simon; Jauregui, Alejandra; Taillie, Lindsey Smith (Annual review of nutrition, 2021)
Countries worldwide have implemented mandatory or voluntary front-of-package nutrition labeling systems. We provide a narrative review of ( ) real-world evaluations of front-of-package nutrition labels that analyze objective sales data and ( ) studies that objectively assess product reformulation in response to a front-of-package nutrition label implementation. We argue that there is sufficient scientific evidence to recommend that governments implement mandatory front-of-package nutrition labeling systems to improvepopulation health. We also present a conceptual framework to describe front-of-package label influence and provide recommendations for the optimal label design, emphasizing that labeling systems should be highly visible and salient, be simple and easy to understand, leverage automatic associations, and integrate informational and emotional messaging. The existing research suggests that Guideline Daily Amount labels should be avoided and that the Health Star Rating and Nutri-Score systems are promising but that systems with warning labels like the one in Chile are likely to produce the largest public health benefits.